2011
DOI: 10.1002/anie.201007598
|View full text |Cite
|
Sign up to set email alerts
|

A Nickel‐Catalyzed Benzannulation Approach to Aromatic Boronic Esters

Abstract: Off and on: A nickel‐catalyzed benzannulation of alkynylboronates provides functionalized phenols with high levels of chemo‐ and regioselectively. While transmetalation of organoboron intermediate to organonickel does not occur during cycloaddition, it is “switched on” by addition of base, thus allowing a one‐pot benzannulation and cross‐coupling to be realized (see scheme; Pin=pinacolato, Ms=mesyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…They also found that both dicarbonylative [3+2] and [4+2] cycloadditions of cyclobutenones and 2‐norbornene could occur, depending on the reaction conditions. Recently, Auvinet and Harrity employed the alkynylboronates as the two‐carbon component for the regioselective benzannulations (via [4+2] cycloadditions and aromatization) with cyclobutenones in the presence of nickel catalyst,13 which provided a facile access to prepare multisubstituted aromatic boronic esters. In 2001, Murakami and Ito developed an efficient route to highly functionalized 1,3‐dienes,14 via a cascade 1,4‐addition of stoichiometric amounts of organometallic reagents/acetate capture/4π‐ring opening mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that both dicarbonylative [3+2] and [4+2] cycloadditions of cyclobutenones and 2‐norbornene could occur, depending on the reaction conditions. Recently, Auvinet and Harrity employed the alkynylboronates as the two‐carbon component for the regioselective benzannulations (via [4+2] cycloadditions and aromatization) with cyclobutenones in the presence of nickel catalyst,13 which provided a facile access to prepare multisubstituted aromatic boronic esters. In 2001, Murakami and Ito developed an efficient route to highly functionalized 1,3‐dienes,14 via a cascade 1,4‐addition of stoichiometric amounts of organometallic reagents/acetate capture/4π‐ring opening mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…The vinylketene [4 þ 2] cycloaddition with boryl-substituted alkynes provided an entry to boryl-substituted phenols. 149 Excellent regioselectivity was observed in most cases when such boryl-substituted alkynes were used.…”
Section: [4 þ 2] Annulationmentioning
confidence: 97%
“…7 More recently, the insertion of alkynylboronates into cyclobutenones has been reported by Auvinet and Harrity. 8 It is noteworthy that in these transformations, cleavage of the less-hindered C-1-C-8 bond is generally observed.…”
Section: Ketone-based Carbon-carbon Bond Activationmentioning
confidence: 98%